2012
DOI: 10.1002/cctc.201200122
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Stereoselective α‐Formylation of Ketones

Abstract: A formal…︁ formyl: N‐Methylbenzothiazolium iodide, a precursor of carbene and an electrophilic compound, has been shown to reacts with the enamine of ketones in a highly enantioselective formylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…29 Based on their previous progress, the group of Cozzi realized an organic aminocatalytic stereoselective formylation of ketones (Scheme 14). 30 The N-methybenzothiazolylium salt 41 is quite electrophilic and reacted with enamine formed from the primary amine Ia and ketone 42 in situ to afford products 43 in moderate yields with high stereoselectivity. This protocol was successful with ketones that incorporate alkyl substituents at the γ ring positions.…”
Section: α-Functionalization Of Carbonyl Compoundsmentioning
confidence: 99%
“…29 Based on their previous progress, the group of Cozzi realized an organic aminocatalytic stereoselective formylation of ketones (Scheme 14). 30 The N-methybenzothiazolylium salt 41 is quite electrophilic and reacted with enamine formed from the primary amine Ia and ketone 42 in situ to afford products 43 in moderate yields with high stereoselectivity. This protocol was successful with ketones that incorporate alkyl substituents at the γ ring positions.…”
Section: α-Functionalization Of Carbonyl Compoundsmentioning
confidence: 99%
“…Cozzi has shown that stabilized carbenium ions can be formed in‐situ from alcohols “on water” 20. The Cozzi group has also demonstrated the direct utilization of naked carbenium ions, such as 1,3‐benzodithiolium,21 benzimidazolium or benzothiazolium cations22 as excellent alkylating agents in the α‐alkylation of aldehydes using organocatalysis. In this case, enamines, which are somewhat less nucleophilic than enolates, were excellent partners for highly reactive carbenium ions.…”
Section: Introductionmentioning
confidence: 99%